2009
DOI: 10.1177/1538192709347847
|View full text |Cite
|
Sign up to set email alerts
|

Parent Involvement in the College Planning Process: A Case Study of P-20 Collaboration

Abstract: Parents who have not had opportunities to attend college themselves have neither experience with the process of college preparation and college going nor sufficient access to needed information. This article describes a collaborative venture between a university department of education and a cluster of local schools designed to help parents of first-generation students become active participants in their children's college preparation and planning, shedding light on the importance of parental involvement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…The above processes may explain why parents with poor education tend to limit young people's tendency to continue schooling beyond what is considered 'reasonable' to achieve (Fann, McClafferty & McDonough 2009;Auerbach 2002;Ceja 2004). Previous research also showed that when disconnected from the system of education themselves, parental support cannot be but vague, evasive, less informed and unreliable (Fann et al 2009;Reid & Moore 2008).…”
Section: Previous Research On 'Under Represented Groups'mentioning
confidence: 99%
See 2 more Smart Citations
“…The above processes may explain why parents with poor education tend to limit young people's tendency to continue schooling beyond what is considered 'reasonable' to achieve (Fann, McClafferty & McDonough 2009;Auerbach 2002;Ceja 2004). Previous research also showed that when disconnected from the system of education themselves, parental support cannot be but vague, evasive, less informed and unreliable (Fann et al 2009;Reid & Moore 2008).…”
Section: Previous Research On 'Under Represented Groups'mentioning
confidence: 99%
“…Previous research also showed that when disconnected from the system of education themselves, parental support cannot be but vague, evasive, less informed and unreliable (Fann et al 2009;Reid & Moore 2008). Besides, parents may not understand the importance of preparation (Reid and Moore 2008) and thus, pressure for short-term, close-to-home and less theoretical degrees.…”
Section: Previous Research On 'Under Represented Groups'mentioning
confidence: 99%
See 1 more Smart Citation
“…contemporary researchers have examined structural barriers to involvement, such as lack of access to computer-based educational information, English language fluency, available child care or time away from work to attend meetings at school, and limited transportation (Green, Walker, Hoover-Dempsey, & sandler, 2007;sosa, 1997). Parents who have not participated in the U.s. postsecondary educational system themselves do not have the same knowledge of the steps and procedures as other parents do (Fann, Jarsky, & McDonough, 2009;Tornatzky, cutler, & Lee, 2002). concerns about documented status, finances, and discrimination are present for some immigrant parents as well (Edwards & Romero, 2008;Motel & Patten, 2013).…”
mentioning
confidence: 99%
“…Scholars have demonstrated that Latino parents prefer to receive educational information in a format that is personal, informal, and includes culturally similar peers with whom they can relate, which is well suited for a group format (Auerbach, 2004;Downs et al, 2008;Fann, Jarsky, & McDonough, 2009). More importantly, psychoeducational group work has often been championed as an effective and culturally relevant intervention for serving individuals from marginalized groups (DeLucia-Waack & Donigian, 2004; Merta, 2006; Start-Rose, Livingston-Sacin, Merchant, & Finley, 2012).…”
mentioning
confidence: 99%